An investigation of sleep patterns in adolescents with high-functioning autism spectrum disorder compared with typically developing adolescents. (June 2013) - Baker, Emma; Richdale, Amanda; Short, Michelle; Gradisar, Michael
<x xml:space="preserve">Abstract</x> Objective: To investigate the sleep patterns and disturbances in a pure sample of adolescents with high-functioning autism spectrum disorder (HFASD). Method: Adolescents completed a sleep questionnaire battery and a 7 d sleep diary. Actigraphic data were collected from a sub-sample of participants (55%) with HFASD and all typically developing (TD) adolescents. Results: Adolescents with HFASD were three times more likely to report a sleep problem than their TD peers (46.2% vs. 14.8%). Adolescents with HFASD had decreased sleep efficiency (diary) (p = 0.04, η2 = 0.10), and more fatigue (p = 0.002, η2 = 0.18) compared with TD adolescents. While TD adolescents generally experienced one symptom of insomnia, adolescents with HFASD were likely to experience two or three symptoms of insomnia (p = 0.02, V = 0.36). Conclusion: The findings suggest that adolescents with HFASD show a continuation of the maladaptive sleep patterns as seen in children with an autism spectrum disorder and these sleep disturbances are associated with increased daytime sleepiness.